Significance of Siglec‐15 expression in colorectal cancer: association with advanced disease stage and fewer tumor‐infiltrating lymphocytes - Zhao Lu; Pu Cheng; Fei Huang; Jiyun Li; Bingzhi Wang; Shuangmei Zou; Zhaoxu Zheng; Chunwei Peng (Wiley, 2023)
Abstract Siglec‐15, a novel immune suppressor, is upregulated in many human cancers. The aim of this study was to explore the expression of Siglec‐15 in colorectal cancer (CRC), and investigate whether Siglec‐15 could be a potential target for cancer immunotherapy in patients with CRC. We performed immunohistochemical analyses of Siglec‐15 on a cohort of 805 patients with CRC and made comparisons between clinicopathological characteristics, PD‐L1 expression, CD3, CD8, CD45RO tumor‐infiltrating lymphocytes (TILs), and prognosis. We found that Siglec‐15 expression was commonly detected in tumor cells (48.3%) and tumor‐associated stromal cells (33.4%), and was more frequently observed than PD‐L1 expression in tumor cells. In contrast, Siglec‐15 expression was weakly and scarcely found in normal mucosa (13%). Siglec‐15 overexpression in tumor cells was associated with advanced TNM stage (p = 0.020). Co‐expression of Siglec‐15 and PD‐L1 in tumor cells was found in 14.4% of patients, and Siglec‐15 expression was detected in almost half of PD‐L1 negative cases. Elevated Siglec‐15 expression in tumor and stromal cells was associated with sparser CD45RO and CD8 TILs (p = 0.035 and p = 0.004, respectively). The expression of Siglec‐15 did not have prognostic significance. In summary, compared to PD‐L1, Siglec‐15 protein expression is more prevalent in CRC and is associated with advanced disease stage and fewer TILs. These findings support Siglec‐15 as a potential cancer immunotherapy target, in addition to PD‐1/PD‐L1 inhibitors, in patients with CRC.